THE EFFECT OF “TEGAR” COMPLEMENTARY EDUCATION PACKAGES ON SELF EFFICACY AND ANXIETY IN POST ABORT MOTHER - Rahmayanti, Rini; Wahyuni, Fitri; Puspasari, Dwi (Universitas Udayana, 2023)
Abortion is a maternal emergency with an incidence of 10-15% of 6 million pregnancies each year. Self efficacy is one of the main factors to improve coping behavior towards perceived loss. The mother's inability to deal with problems causes prolonged grief and affects future health, so efforts are needed to increase self-efficacy and reduce maternal anxiety. Mother's self-efficacy and anxiety are influenced by knowledge. Increased knowledge can be done by providing a complementary package of interventions